Perceptions and culture of safety among helicopter emergency medical service personnel in the UK. Issue 11 (20th June 2016) - Chesters, Adam; Grieve, Philip H; Hodgetts, Timothy J
Abstract : Background: The use of helicopter emergency medical services (HEMS) has increased significantly in the UK since 1987. To date there has been no research that addresses HEMS pilots and medical crews' own ideas on the risks that they view as inherent in their line of work and how to mitigate these risks. The aim of this survey is to describe and compare the attitudes and perceptions towards risk in HEMS operations of these staff. Methods: A questionnaire was administered electronically to a representative selection of HEMS doctors, paramedics and pilots in the UK. A number of questions were grouped into common themes, and presented as Likert scales and ranking where appropriate. Descriptive and comparative results were presented and statistically analysed. Results: The target sample of 100 consecutive respondents was achieved. All questionnaires were entirely completed. Respondents attributed the most risk to night HEMS operations without the use of night vision goggles, commercial pressure and mechanical aircraft failure. There was no statistical difference in overall perception of safety and years of experience (p=0.58) or between professions (p=0.08). Those who had experienced a crash were more likely to believe that HEMS operations are not inherently safe (p=0.05). Conclusions: We have surveyed a cross-section of the HEMS operational community in the UK in order to describe their perceptions of safety and risk within their professional life. Two-thirds of respondents believed that HEMS operations were inherently safe. Those who did not seemed to be influenced by personal experience of a crash or serious incident. We support increased operational training for clinical crewmembers, an increased emphasis on incident reporting and a culture of safety, and careful attention to minimum training and equipment requirements for all HEMS missions.